Cell-type specific expression of the vasopressin gene analyzed by AAV mediated gene delivery of promoter deletion constructs into the rat SON in vivo. - Todd A Ponzio; Raymond L Fields; Omar M Rashid; Yasmmyn D Salinas; Daniel Lubelski; Harold Gainer (PLoS ONE, 2012)
The magnocellular neurons (MCNs) in the supraoptic nucleus (SON) of the hypothalamus selectively express either oxytocin (Oxt) or vasopressin (Avp) neuropeptide genes. In this paper we examine the cis-regulatory domains in the Avp gene promoter that are responsible for its cell-type specific expression. AAV vectors that contain various Avp gene promoter deletion constructs using EGFP as the reporter were stereotaxically injected into the rat SON. Two weeks following the injection immunohistochemical assays of EGFP expression from these constructs were done to determine whether the expressed EGFP reporter co-localizes with either the Oxt- or Avp-immunoreactivity in the MCNs. The results identify three major enhancer domains located at -2.0 to -1.5 kbp, -1.5 to -950 bp, and -950 to -543 bp in the Avp gene promoter that regulate the expression in Avp MCNs. The results also show that cell-type specific expression in Avp MCNs is maintained in constructs containing at least 288 bp of the promoter region upstream of the transcription start site, but this specificity is lost at 116 bp and below. Based on these data, we hypothesize that the -288 bp to -116 bp domain contains an Avp MCN specific activator and a possible repressor that inhibits expression in Oxt-MCNs, thereby leading to the cell-type specific expression of the Avp gene only in the Avp-MCNs.